PENERAPAN MEDIA PEMBELAJARAN FIQIH BERBASIS AUDIO VISUAL DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS VII A MTS NEGERI 2 WONOGIRI TAHUN AJARAN 2022/2023 - Hasanah, Uswatun; Sukari, S; Sugiyat, S (Al’ulum Jurnal Pendidikan Islam, 2024)
This research aims to determine the application of audio-visual learning media in increasing the learning motivation of grade 7 MTs students. This type of research is qualitative with a descriptive approach. The entire population of children aged 12-13 years was selected as the class 7A sample. The research results concluded that audio, visual and audio-visual learning media were effectively used to improve students' understanding of the material. The use of audio-visual media such as films makes learning more interesting, motivating and eliminates boredom in the process of learning the fiqh material presented by the teacher. Future developments require the development of media innovation, such as the use of animated films, Android applications for fiqh material, and many other interactive media needed for learning fiqh material.